Impact of CSA technology packages on smallholder farmers under the accelerator program in Zambia - Homann-Kee Tui, Sabine; Kakwasha, Keagan; Wilkinson, Melanie; Chongo, Collins; Hang'ombe, M.B.; Zulu, Samuel; Mubanga, Casco; Moyo, Martin; Jacobs-Mata, Inga (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The primary goal of this report is to provide evidence on the impact of CSA technology packages on smallholder farmers under the accelerator programme in in Zambia. The AICCRA Zambia accelerator program tested various CSA technology packages, designed and implemented through agribusiness partnerships, SME bundles. The SME bundles were selected through a competitive process for the packages to address major challenges for CSA in Zambia and covering major agricultural production systems in Zambia. Each bundle was supported by a 50,000-USD grant.